2007
DOI: 10.1007/s11948-007-9048-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Sensemaking Approach to Ethics Training in the Physical Sciences and Engineering

Abstract: Integrity is a critical determinant of the effectiveness of research organizations in terms of producing high quality research and educating the new generation of scientists. A number of responsible conduct of research (RCR) training programs have been developed to address this growing organizational concern. However, in spite of a significant body of research in ethics training, it is still unknown which approach has the highest potential to enhance researchers' integrity. One of the approaches showing some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 73 publications
(77 reference statements)
1
41
0
2
Order By: Relevance
“…Given a lack of standardization for these ''codes,'' we included general frameworks of ethical rules or principles in the present study. Second, evidence from other domains of instruction has shown that educating individuals on problems, and methods to work through or resolve these problems (i.e., strategies), has been effective (Kligyte et al, 2008;Mumford et al, 2008;Scott et al, 2004). Thus, we sought to examine if and how instructional programs built around typical problems in ethical decision-making and general strategies for working through ethical problems would moderate the effectiveness of ethics instruction.…”
Section: Instructional Contentmentioning
confidence: 99%
“…Given a lack of standardization for these ''codes,'' we included general frameworks of ethical rules or principles in the present study. Second, evidence from other domains of instruction has shown that educating individuals on problems, and methods to work through or resolve these problems (i.e., strategies), has been effective (Kligyte et al, 2008;Mumford et al, 2008;Scott et al, 2004). Thus, we sought to examine if and how instructional programs built around typical problems in ethical decision-making and general strategies for working through ethical problems would moderate the effectiveness of ethics instruction.…”
Section: Instructional Contentmentioning
confidence: 99%
“…The original RCR training curriculum was adapted for professionals specializing in the physical sciences and engineering by emphasizing the interactive nature of the intervention through the combination of lecture, discussion, and experiential exercises [45]. The training consisted of ten modules primarily focused on discussing the complexity of ethical decision-making and the limitations of a rulebased approach in highly complex and ambiguous ethical situations; common reasoning errors in decision-making (e.g., personal biases); and metacognitive reasoning strategies that help address typical reasoning errors [45].…”
Section: Sensemaking Trainingmentioning
confidence: 99%
“…The training consisted of ten modules primarily focused on discussing the complexity of ethical decision-making and the limitations of a rulebased approach in highly complex and ambiguous ethical situations; common reasoning errors in decision-making (e.g., personal biases); and metacognitive reasoning strategies that help address typical reasoning errors [45]. For a more detailed description of the RCR training content see Kligyte et al [45].…”
Section: Sensemaking Trainingmentioning
confidence: 99%
See 2 more Smart Citations